F47 Exploring emotion regulation and emotion recognition in people with presymptomatic huntington's disease: the role of emotional awareness. (September 2018) - Zarotti, Nicolò; Simpson, Jane; Fletcher, Ian; Squitieri, Ferdinando; Migliore, Simone
Abstract : Interest in the role of both emotion regulation and recognition in our understanding of mental health has been steadily increasing, especially in people with chronic illness who also have psychological difficulties. One illness which belongs to this category is Huntington's disease. Huntington's disease (HD) is a chronic neurodegenerative disorder that can cause a number of cognitive and psychological difficulties, including emotion recognition deficits, even before the onset of the symptoms required to make a formal diagnosis. Despite the lack of definite evidence, recent studies have suggested that deficits of emotion regulation and recognition may be expected to play a pivotal role in the early cognitive manifestations of HD. In this study, we hypothesised that the ability to regulate emotions can be impaired in people with pre- symptomatic HD, and that such impairment may be associated with a deficit of emotion recognition. To test this, an online survey was carried out with 117 English and Italian-speaking people with presymptomatic HD, compared to 217 controls matched for age and education. The results suggest that, in presymptomatic participants, emotion regulation and emotion recognition are generally not significantly impaired, and no significant relationships between performances on the two constructs were observed. However, a specific impairment in emotional awareness (a subscale on the Difficulties in Emotion Regulation Scale, DERS) was observed, which appears to be enhanced by the co-occurrence of de- pressive symptoms, even at a subclinical level. Consequently, it is suggested that difficulties in emotional awareness may represent a precursor of more general emotion recognition impairments, which only become apparent as the disease reaches a more symptomatic level. Clinical implications of the findings are discussed and directions for future research are proposed.